Penerapan Model Pembelajaran Talking Stick untuk Meningkatkan Hasil Belajar Siswa Tentang Keterampilan Membaca - Hasnah Hasnah; Lukman Lukman; Syarmilah Syarmilah (STKIP Andi Matappa Pangkep, 2023)
The problem in this study is the low process and learning outcomes of class V students. This study aims to determine the improvement of student learning processes and outcomes. This study uses a qualitative approach and the type of research used is PTK. The subjects in this study were teachers and fifth grade students of UPT SD Negeri 118 Kotu for the 2022/2023 academic year, a total of 11 students consisting of 7 boys and 4 girls. Based on observations of teachers in cycle I and cycle II, the level of success obtained was the category good (B). Likewise with student activities during the learning process in cycle I and cycle II which have been going well so that good categories are obtained (B. cycle I with the average value of learning outcomes obtained by students in the category (C), in cycle II it has again increased with the category good (B) The conclusion in this study is that the application of the talking stick learning model can improve the process and student learning outcomes regarding reading skill fiction and nonfiction class V UPT SD Negeri 118 Kotu.